A genome‐wide association study suggests that MAPK14 is associated with diabetic foot ulcers. (1st December 2017) - Meng, W.; Veluchamy, A.; Hébert, H.L.; Campbell, A.; Colhoun, H.M.; Palmer, C.N.A.
Summary: Background Diabetic foot ulcers (DFUs) are a devastating complication of diabetes. Objectives To identify genetic contributors to the development of DFUs in the presence of peripheral neuropathy in a Scottish cohort with diabetes using a genome‐wide association study. Methods A genome‐wide association approach was applied. A case was defined as a person with diabetes (type 1 or type 2) who had ever had a foot ulcer (current or previous) in at least one foot, as well as a positive monofilament test result (i.e. evidence of peripheral neuropathy) recorded in their longitudinal e‐health records. A control was defined as an individual with diabetes (type 1 or type 2) who has never been recorded as having a foot ulcer in either foot but who had a positive monofilament test result recorded in either foot in their longitudinal e‐health records. Results There were 699 DFU cases and 2695 controls in the Genetics of Diabetes Audit and Research in Tayside Scotland (GoDARTS) dataset. The single‐nucleotide polymorphism rs80028505 (Chr6p21·31) in MAPK14 reached genome‐wide significance with a lowest P ‐value of 2·45 × 10 −8 . The narrow‐sense heritability of this phenotype is 0·06. Conclusions We suggest that MAPK14 is associated with DFUs.